The 2-Dimensional World of Graphene - Khanna, Virat; Chaudhary, Vishal; Munawar, Anam; Umapathi, Reddicherla; Singh, Kamaljit (Bentham Science Publishers, 2024)
The 2-Dimensional World of Graphene explores a wide range of graphene applications, capturing current research and understanding about the material while also offering a glimpse into the exciting possibilities that lie ahead. It compiles 10 edited reviews contributed by experts in chemistry. The book begins with a comparison of short-chain dyad graphene oxide and graphene quantum dot nanocomposites, highlighting their role in renewable energy. The introductory chapter is followed by reviews on graphene applications forensics, water purification, green synthesis from agricultural waste, energy storage and conversion, reliability engineering and advanced material fabrication. Each chapter includes structured sections, detailed references and a summary for a broad readership. Contributors have included information on structures and relevant methodology where appropriate for the range of applications highlighted. The 2-Dimensional World of Graphene is an essential primer on applications of graphene and its derivatives.